1998
DOI: 10.1007/s002669900228
|View full text |Cite
|
Sign up to set email alerts
|

“Flip-Flap” Mastopexy

Abstract: The "flip-flap" mastopexy modifies the McKissock vertical bipedicle design by creating a wide superiorly based flap of breast tissue deep to the vertical bipedicle. Transposition of this flap up and beneath the upper breast, with suture anchoring to the pectoralis fascia at the level of the second rib, restores upper breast fullness, decreases mastopexy-wrecking lower breast bulk, and provides a pleasant forward thrust of the nipple-areolar complex. The "flip-flap" is effective for improving the long-term aest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This observation concurs with Flowers' [ 17 ] suggestion. He noticed that most mastopexy operations leave heavy breast bulk remaining in the lower pole of the breast.…”
Section: Discussionsupporting
confidence: 92%
“…This observation concurs with Flowers' [ 17 ] suggestion. He noticed that most mastopexy operations leave heavy breast bulk remaining in the lower pole of the breast.…”
Section: Discussionsupporting
confidence: 92%
“…The formation of fibrous tissue by an internal mesh support can also be used to achieve a more stable result, as shown by Goes. 13 Using permanent mesh grafts in an organ prone to cancer and therefore requiring Pitanguy 30 Inverted-T scar 317 Ptosis Wise 6 Inverted-T scar Not reported None reported Nicolle and Chir 31 Inverted-T scar Over 400 Scar widening, hypertrophic lateral scar Peixoto 28 Inverted-T scar Not reported Scar too long with incorrect measurements Flowers and Smith 29 Inverted-T scar 124 Localized tissue necrosis Strombeck 25 Inverted-T scar 37 Hematoma, widening of scars, ptosis, skin necrosis Marchac and de Olarte 26 Inverted-T scar 77 Hematoma Lassus 17,18 Vertical scar 433 Scar hypertrophy Lejour 15,16 Vertical scar Not reported Not reported Hammond 19 Vertical scar Not reported Partial areolar necrosis, fat necrosis, delayed wound healing, purse-string rupture, exposed purse-string suture Marconi 21 Vertical scar 5 Not reported Seidel and Chiari 33 L-scar Not reported Flat shape, enlarged nipple-areola complex Regnault 35 L-scar Not reported Partial loss of areola Erol and Spira 8 Periareolar scar 6 Delayed wound healing Spear 10,11 Periareolar scar Not reported Seroma, foreign-body reaction, decreased nipple sensation Goes 13 Periareolar scar 254 Hematoma, seroma, fat necrosis, decreased nipple sensation Benelli 3,4 Periareolar scar 73, 69 with augmentation Hematoma, cystosteatonecrosis Bartels et al 14 Periareolar scar Not reported Stretching, flattening of areola Puckett 12 Periareolar scar 26 Scar widening, globular breast shape, enlargement of areola Gruber 9 Periareolar scar Not reported Not reported regular examination is problematic. Suspending breast tissue by means of a muscle loop has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…29 Pitanguy 30 uses a lozengeshaped glandular resection (Arie-Pitanguy), and a keel resection for severe ptosis. 30 For glandular reshaping, Nicolle and Chir 31 dissect medially and superiorly and then dissect the breast from the pectoralis muscle.…”
Section: Inverted-t Scar Techniquementioning
confidence: 99%
“…The advantage here is that this mobilized gland, responsible for breast projection, does not interfere with NAC lift and vascularization which is still maintained on an independent superior pedicle. The second type of autoaugmentation consists in advancing a superiorly or superomedially based glandular flap (8)(9)(10). The technique's main advantage lies in the lower rate of bottoming out, since most of the breast weight is not lying in its inferior part.…”
Section: Dear Sirmentioning
confidence: 99%